Dimethyl fumarate‐induced lymphocyte count drop is related to clinical effectiveness in relapsing–remitting multiple sclerosis. (17th October 2020) - Tsantes, E.; Curti, E.; Ferraro, D.; Lugaresi, A.; Baldi, E.; Montepietra, S.; Immovilli, P.; Simone, A. M.; Mancinelli, L.; Strumia, S.; Vitetta, F.; Foschi, M.; et al.
Abstract : Background and purpose: Dimethyl fumarate (DMF) causes a mean lymphocyte count drop of approximately 30% in relapsing–remitting multiple sclerosis (RRMS) patients. The relationship between this reduction and DMF effectiveness is controversial. The objective was to investigate if the decrease in absolute lymphocyte count (ALC) from baseline during DMF treatment is associated with clinical and magnetic resonance imaging (MRI) disease activity. A secondary aim was to evaluate ALC variations over time in a real‐life cohort of DMF‐treated patients. Methods: Demographic, laboratory, clinical and MRI data were collected in this observational multicentre study, conducted on RRMS patients treated with DMF for at least 6 months. Multivariate Cox models were performed to evaluate the impact of 6‐month ALC drop on time to no evidence of disease activity (NEDA‐3) status loss. NEDA‐3 is defined as absence of clinical relapses, MRI disease activity and confirmed disability progression. Results: In all, 476 patients (312 females, age at DMF start 38.4 ± 9.97 years) were analysed up to 5‐year follow‐up. A greater lymphocyte decrease was associated with a lower risk of NEDA‐3 status loss (hazard ratio 0.87, P = 0.01). A worse outcome in patients with lower ALC drop (<11.5%), compared with higher tertiles (11.5%–40.5% and >40.5%), was observed ( P = 0.008). The nadir of ALC drop (−33.6%) and 35% of grade III lymphopaenia cases occurred after 12 months of treatment. Conclusion: A higher lymphocyte count drop at 6 months is related to better outcomes in DMF‐treated patients. A careful ALC monitoring should be pursued up to 24 months of treatment. Abstract : The association between lymphocyte count drop during dimethyl fumarate (DMF) treatment and drug's effectiveness in multiple sclerosis patients is controversial. Our results show that a greater lymphocyte drop at six months is associated with a lower risk of NEDA‐3 status loss in DMF‐treated patients. NEDA‐3 ("no evidence of disease activity") is defined as absence of clinical relapses, MRI disease activity and disability progression. A worse outcome in patients with lower ALC drop (< 11.5%), compared with higher tertiles (11.5–40.5% and > 40.5%), was observed ( P = 0.008). Moreover, we found that the nadir of ALC drop occurred after 12 months of treatment.